Research Advances for Virus-vectored Tuberculosis Vaccines and Latest Findings on Tuberculosis Vaccine Development - Hu, Zhidong; Lu, Shui-Hua; Lowrie, Douglas B.; Fan, Xiao-Yong (Frontiers in Immunology, 2022)
Tuberculosis (TB), caused by respiratory infection with Mycobacterium tuberculosis, remains a major global health threat. The only licensed TB vaccine, the one-hundred-year-old BCG has variable efficacy and often provides poor protection against adult TB, the transmissible form of the disease. Thus, the lack of an optimal TB vaccine is one of the barriers to TB control. Recently, the development of highly efficacious COVID-19 vaccines within one year accelerated the vaccine development process in human use, with the notable example of mRNA and adenovirus-vectored vaccines, and increased the public acceptance of the concept of controlled human challenge model. In the TB vaccine field, recent progress also facilitated the deployment of an effective TB vaccine. In this review, we provide an update on the current virus-vectored TB vaccine pipeline and summarize the latest findings that might facilitate TB vaccine development. In detail, on the one hand, we provide a systematic literature review of the virus-vectored TB vaccines are in clinical trials, and other promising candidate vaccines at an earlier stage of development are being evaluated in preclinical animal models. These research sharply increase the likelihood of finding a more effective TB vaccine in the near future. On the other hand, we provide an update on the latest tools and concept that facilitating TB vaccine research development. We propose that a pre-requisite for successful development may be a better understanding of both the lung-resident memory T cell-mediated mucosal immunity and the trained immunity of phagocytic cells. Such knowledge could reveal novel targets and result in the innovative vaccine designs that may be needed for a quantum leap forward in vaccine efficacy. We also summarized the research on controlled human infection and ultra-low-dose aerosol infection murine models, which may provide more realistic assessments of vaccine utility at earlier stages. In addition, we believe that the success in the ongoing efforts to identify correlates of protection would be a game-changer for streamlining the triage of multiple next-generation TB vaccine candidates. Thus, with more advanced knowledge of TB vaccine research, we remain hopeful that a more effective TB vaccine will eventually be developed in the future.